KONSEP AMACCANG MASYARAKAT BUGIS DALAM PERSPEKTIF FILSAFAT PENDIDIKAN - , ISKANDAR ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The study entitled, The Concept of Amaccang of Bugis Society in Philosophy of Education Perspective, is driven from the thoughtfulness of the erratic educational condition in Indonesia and the easy entrance of foreign cultural values into community life without any appropriate selection based national cultures. As a result, local cultural values are ignored and replaced by the Western cultural values which are irrelevant to the national cultures. The main purpose of this study is to describe and understand the nature of Bugis education, the concept of amaccang, in the philosophy of education perspective. Not just as a local wisdom, the concept of amaccang also has educational values which can be used as a reference in the quality improvement of education in Indonesia. This study is a type of literature or library research. Material object in this study is the Concept of amaccang in Bugis society, while the formal object used as an analytical tool is the Philosophy of Education. The method used is hermeneutics. In addition to hermeneutics, heuristics method is used as well. Heuristic method used is related to the relevance of the concept of amaccang towards the development of education in Indonesia with its methodological studies elements namely descriptive, interpretation, and verstehen. The results obtained in this study are (1) the essence of the concept of amaccang in Bugis society as a culture, (2) the contribution of amaccang concept towards the development of education in Indonesia, (3) the relevance of amaccang concept in Bugis society for the development of education in Indonesia is one of the findings which has important roles in educational development in Indonesia where those values are extracted from the Indonesian nation, in this case, the Bugis. Related to the findings about the values of local wisdom towards the real development of education in Indonesia, those values need to be implemented within the next generation. The values are